Supersymetria - nauka czy fantazja - Tempczyk, Michał (Filozofia Nauki, 2006)
Elementary particle physics is an intensively developing fundamental branch of physics. It has many important results and the picture of the fundamental level of the structure of matter elaborated by this theory becomes more and more detailed and complete. Physicists call the picture the Standard Model. However, in spite of its great achievements, Standard Model has several serious problems that cannot be solved by its methods. In order to overcome these problems physicists formulate the ultimate physical theory, called the supersymmetry theory. They have big expectations with respect to this theory and they build strong accelerators to perform experiments testing specific predictions of supersymmetry. Till now none of those predictions has been empirically corroborated and this fact leads to the conclusion that the idea of supersymmetry is more fantasy than the empirical scientific theory. The paper is based on the presentation of the supersymmetry theory given by G. Kane in his book Supersymmetry. Squarks, Photinos and the Unveilling of the Ultimate Laws of Nature.